2019
DOI: 10.1128/aem.00217-19
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Free-Living and Particle-Associated Vibrio Communities in the Northern Chinese Marginal Seas

Abstract: Vibrio species are associated with human health and play important roles in the carbon cycle. The interest in the Vibrio ecology in marine pelagic environments has increased in recent years, and the correlations between the Vibrio community structure and various environmental factors have been demonstrated. However, the identification of planktonic Vibrio species and their relationship with particulate matter are unclear. Here, we elucidated the spatiotemporal dynamics of Vibrio diversity and in relation to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 56 publications
8
72
1
Order By: Relevance
“…The relation of non-culturable forms of Vibrio with the organic matter was closer during the post-monsoon as indicated by the CCA. Vibrio species tend to form biofilms in the SPM and display several enzymes for organic matter remineralization (Neogi et al, 2018;Liang et al, 2019). The particulates offer also protection from predation and unfavorable environmental conditions and sometimes are described as islands sheltering pathogenic organisms in the form of biofilms.…”
Section: Vibrio Dynamic: Culturability and Influence Of The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The relation of non-culturable forms of Vibrio with the organic matter was closer during the post-monsoon as indicated by the CCA. Vibrio species tend to form biofilms in the SPM and display several enzymes for organic matter remineralization (Neogi et al, 2018;Liang et al, 2019). The particulates offer also protection from predation and unfavorable environmental conditions and sometimes are described as islands sheltering pathogenic organisms in the form of biofilms.…”
Section: Vibrio Dynamic: Culturability and Influence Of The Environmentmentioning
confidence: 99%
“…Vibrio species tend to form biofilms in seston and present a wide variety of enzymes to degrade and assimilate organic matter playing unique roles in biogeochemical cycles (Lara et al, 2011;Neogi et al, 2018;Liang et al, 2019). Moreover, Vibrio populations interact with other microorganisms during the process of nutrient remineralization, which is performed by a variety of microbial taxa with different metabolic and physiological capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…All those factors led to high production and degradation rates in summer. In addition, Liang et al (2019) also found that the dominant bacteria groups exhibited different distributions in abundance with different seasons and sea areas. Specifically, the abundance of V. campbellii was higher in the YS than in the BS in summer (p < 0.05), whereas the abundance of V. caribbeanicus drastically decreased from the BS to the YS (p < 0.05).…”
Section: Degradation Of Dmspd and Aad In The Bs And Ysmentioning
confidence: 92%
“…In addition, the seasonal differences in bacteria abundance and light intensity also made great contributions to different rates of microbial degradation and photochemical degradation, respectively. According to Liang et al (2019), the abundances of Vibrio (belonging to the class γ -proteobacteria) averaged 1.4 × 10 6 copies L −1 in summer, which was significantly higher than in winter (mean value of 1.9 × 10 5 copies L −1 ) (Mann-Whitney test, p < 0.01). Significant seasonal differences in total bacterial abundance were also observed (Mann-Whitney test, p < 0.001).…”
Section: Degradation Of Dmspd and Aad In The Bs And Ysmentioning
confidence: 99%
See 1 more Smart Citation